Strategy to Improve Understanding of Prospective Brides Through Empowering Health Cadres (Smart Katin) - Fidyawati Aprianti A. Hiola; Dwi Nur Octaviani Katili (Journal La Medihealtico, 2026)
Planning Agency (BKKBN), approximately 1.7 million couples marry each year, and more than 40% of them lack a basic understanding of premarital health, such as nutrition, reproductive health, mental health, and family planning. Conventional one-way education methods are often ineffective, necessitating a community-based approach. The Health Cadre Intervention is offered as an alternative strategy that leverages the cadre's social proximity to the prospective bride and groom to increase understanding. This study used a pre-experimental design with a pretest- posttest model without a control group. The sample consisted of 30 respondents, the majority of whom were aged 20–35 (93.3%), female (86.7%), and had secondary education (63.3%). A knowledge questionnaire was administered before and after the intervention. The data were analyzed using the Wilcoxon test to assess differences in understanding scores. The results showed an increase in the average score from 90.17 (SD = 7.87) in the pretest to 96.70 (SD = 5.24) in the posttest . The Wilcoxon test yielded a Z-value of -4.29 with p < 0.001, indicating a significant difference. Eighty percent of respondents experienced an increase in their scores, 20% remained in the good category, and none experienced a decrease. The KATIN CERDAS intervention has proven effective in improving prospective brides and grooms' understanding of reproductive health. This cadre-based strategy can be integrated into premarital counseling programs in primary care to support the formation of healthy families and prevent reproductive health problems early on.